A new species of Neobaryssinus Monné & Martins, and two new species of Baryssiniella new genus (Coleoptera: Cerambycidae), reared from trees in the Brazil nut family (Lecythidaceae) - Berkov, Amy; Monné, Miguel A. (Zootaxa, 2010)
Neobaryssinus altissimus new species is described from central French Guiana; a key to the four species of the genus is given. Baryssiniella new genus is described, including two new species: B. hieroglyphica new species from southeastern Peru, and B. tavakiliani new species from central French Guiana. Comparisons among Neobaryssinus, Baryssiniella, and several other genera in the tribe Acanthocinini are presented. All three new species were reared from trees in the Brazil nut family (Lecythidaceae). Two of these species emerged preferentially from bait branches at canopy stratum.